Cardiovascular safety of naltrexone and bupropion therapy: Systematic review and meta‐analyses. (12th April 2021) - Sposito, Andrei C.; Bonilha, Isabella; Luchiari, Beatriz; Benchimol, Alexander; Hohl, Alexandre; Moura, Fabio; Cercato, Cíntia; Geloneze, Bruno; Nadruz, Wilson; Aguilar‐Salinas, Carlos; Carvalho, Luiz Sergio F.
Summary: Despite being approved for clinical use, evidence of cardiovascular safety (CV) is lacking for treatment with bupropion, naltrexone, or their combination (B‐N). The purpose of the study is to determine the relationship between these treatments and the risk of major cardiovascular adverse events (MACE). Phase 3 randomized clinical trials (RCT) evaluating bupropion, naltrexone, or B‐N versus control with reported incidence of MACE. The meta‐analysis included 12 RCTs, 69% for weight loss and 29% for smoking cessation, with 19, 176 patients and 7354 patient‐years who were randomized to an active treatment (bupropion [ n = 2965] or B‐N [ n = 6980] or naltrexone [ n = 249]) versus control (placebo [ n = 6968] or nicotine patch [ n = 2014]). The mean age was 54 ± 8 years (55% female), and the baseline BMI was 32 ± 5 kg/m 2 . The additive network meta‐analysis model for random effects showed no association between bupropion, B‐N, or naltrexone and MACE (odds ratio [OR] = 0.90 [95%CI 0.65–1.25], p = 0.52; OR = 0.97 [95%CI 0.75–1.24], p = 0.79; OR = 1.08 [95%CI 0.71–1.63], p = 0.73, respectively; I 2 = 0%, p = 0.86). Meta‐regression analyses showed no significant association between MACE and potential confounders from RCT demographic disparities ( p = 0.58). The statistical power (post hoc two‐tailed) for non‐inferiority was 91%, giving a strong probability of validity. Naltrexone, bupropion, or B‐N is not associated with the incidence of MACE as compared with placebo.